Advanced remote sensing : terrestrial information extraction and applications - Liang, Shunlin; Li, Xiaowen, 1969-; Wang, Jindi (Amsterdam ; Boston : Academic Press, 2012)
"Advanced Remote Sensing is an application-based reference that provides a single source of mathematical concepts necessary for remote sensing data gathering and assimilation. It presents state-of-the-art techniques for estimating land surface variables from a variety of data types, including optical sensors such as RADAR and LIDAR. Scientists in a number of different fields including geography, geology, atmospheric science, environmental science, planetary science and ecology will have access to critically-important data extraction techniques and their virtually unlimited applications. While rigorous enough for the most experienced of scientists, the techniques are well designed and integrated, making the book's content intuitive, clearly presented, and practical in its implementation"--
Machine generated contents note: 1. A Systematic View of Remote Sensing 2. Geometric Processing and Positioning Techniques 3. Compositing, Smoothing and Gap-filling Techniques 4. Data Fusion 5. Atmospheric Correction of Optical Imagery 6. Solar Radiation 7. Broadband Albedo 8. Land Surface Temperature and Thermal Infrared Emissivity 9. Surface Longwave Radiation Budget 10. Canopy Biochemical Characteristics 11. Leaf Area Index 12. Fraction of Absorbed Photosynthetically Active Radiation by Green Vegetation 13. Fractional Vegetation Cover 14. Vegetation Height and Vertical Structure 15. Above-ground Biomass 16. Vegetation production in terrestrial ecosystems 17. Precipitation 18. Terrestrial Evapotranspiration 19. Soil Moisture 20. Snow Water Equivalence 21. Water Storage 22. High-level Land Product Integration Methods 23. Product and Data Management Systems 24. Land Cover and Land Use Changes.
Includes bibliographical references and index.
Keywords: Earth sciences -- Remote sensing; Environmental sciences -- Remote sensing; Remote sensing